Исследование альфа- и бета-полей в приземной атмосфере - Черепнев М. С. Максим Святославович; Вуколов А. В. Артем Владимирович; Ипполитов И. И. Иван Иванович; Кабанов М. В. Михаил Всеволодович; Нагорский П. М. Петр Михайлович; Смирнов С. В. Сергей Васильевич; Яковлева В. С. Валентина Станиславовна (Секция D. Физика атмосферы, 2013)
Заглавие с экрана